Comparison of TVUS, MRI, and Frozen Section Methods in Preoperative Detection of Myometrial Invasion in Patients with Endometrial Cancer - Hasim Kural; Ercan Yilmaz; Rauf Melekoglu; Aysenur Akatli; Leyla Karaca (Acta Clinica Croatica, 2021)
We aimed to evaluate the depth of myometrial invasion preoperatively with transvaginal ultrasound, magnetic resonance imaging, and frozen section examination techniques in patients diagnosed with endometrial cancer. Our study included 65 patients. Transvaginal ultrasound and magnetic resonance imaging were performed in study patients in the preoperative period. Frozen section examination was performed in all hysterectomy samples obtained from all study patients. Data were analyzed with SPSS Statistics 22.0 program. The sensitivity of transvaginal ultrasound in determining the depth of myometrial invasion was 88.64%, specificity 90.48%, positive predictive value 95.12%, and negative predictive value 79.17%. For magnetic resonance imaging, the sensitivity was 63.64%, specificity 95.24%, positive predictive value 96.55%, and negative predictive value 55.56%. In addition to the frozen section examination, which is the gold standard in determining the myometrial invasion depth, transvaginal ultrasound and magnetic resonance imaging have become commonly used methods for this purpose in recent years. Ultrasound examination performed by an experienced specialist is superior to magnetic resonance imaging as it is fast, inexpensive, and associated with higher sensitivity.